THE CHARACTER DISCOURSE OF MINANGKABAU CULTURE (MATRILINEAL) IN GUS TF SAKAI'S NOVEL AND SHORT STORIES - Fadlillah Fadlillah (International Conference on Languages and Arts, 2014)
Matrilineal Minangkabau culture are in marginalized and subjected to violent attacks in the vortex of globalization epistemic capitalistic culture. Thus, the principal issue is how the matrilineal Minangkabau culture character discourse in the target epistemic violence in the literary works of Gus tf Sakai. The violence is at the facts that are not able to disclosed historical, social and political over the years, but it is only disclosed literature. One is the issue of humanitarian discourse on culture. Literature is a cultural issue to be explored, dismantled and examined; about "something" behind all of it, which must be read, there is data and facts in it, which had been hidden. All it allows to be explored in the study of cultural studies and postpositivistik, the postmodern paradigm. This study used the theory of deconstruction Derrida, intertextual Kristeva, Foucault's discourse to unpack and read the cultural discourse. With this study found a form of matrilineal Minangkabau culture character egaliti, and independent community, but has become a flake due to epistemic violence. Stunami happened already knocked down culture of Minangkabau culture.   Keywords: cultural studies, discourse, character matrilinael culture.